2015
DOI: 10.1021/la504020e
|View full text |Cite
|
Sign up to set email alerts
|

Complex Equilibria, Speciation, and Heteroprotein Coacervation of Lactoferrin and β-Lactoglobulin

Abstract: There has been a resurgence of interest in complex coacervation, a form of liquid-liquid phase separation (LLPS) in systems of oppositely charged macroions, but very few reports describe the somewhat anomalous coacervation between acidic and basic proteins, which occurs under very narrow ranges of conditions. We sought to identify the roles of equilibrium interprotein complexes during the coacervation of β-lactoglobulin dimer (BLG2) with lactoferrin (LF) and found that this LLPS arises specifically from LF(BLG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…The qualitative nature of turbidity-style measurements allows a phenomenological characterization of coacervate phase behavior, rather than a more direct quantification of the binodal phase space [8,15,71,[73][74][75][76][77]83,88,[91][92][93]104,105,108,112,114,. Typical characterization experiments include evaluation of the stoichiometric ratio of polycation to polyanion, the effect of increasing salt concentration, and the effect of variable pH.…”
Section: Connecting Coacervate Phase Behavior With Materials Dynamicsmentioning
confidence: 99%
“…The qualitative nature of turbidity-style measurements allows a phenomenological characterization of coacervate phase behavior, rather than a more direct quantification of the binodal phase space [8,15,71,[73][74][75][76][77]83,88,[91][92][93]104,105,108,112,114,. Typical characterization experiments include evaluation of the stoichiometric ratio of polycation to polyanion, the effect of increasing salt concentration, and the effect of variable pH.…”
Section: Connecting Coacervate Phase Behavior With Materials Dynamicsmentioning
confidence: 99%
“…As illustrated in Fig. 2, LF exhibits two unequal positive domains on its surface capable of binding two β-LG 2 with different affinities [64].…”
Section: Primary Units Of the Coacervatesmentioning
confidence: 99%
“…These molecular species are attributed to different LF/β-LG complexes: LF(β-LG 2 ), LF(β-LG 2 ) 2 , LF 2 (β-LG 2 ) ranked in ascending Rh order. Only one of these complexes, LF(β-LG 2 ) 2 , was suggested to be involved in the coacervate structure [64]. By changing the protein mixing ratio away from the optimal value for coacervation, it was suggested that the stoichiometry of LF/β-LG complexes is modified and the coacervation yield decreases due to a lower abundance of LF(β-LG 2 ) 2 [64].…”
Section: Primary Units Of the Coacervatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the coacervation of two whey proteins, betalactoglobulin (BLG) and lactoferrin (LF), have been investigated in details (Anema & de Kruif, 2014;Flanagan et al, 2015;Yan et al, 2013). Beyond their ability to form coacervates, whey proteins display other features that are interesting from industrial and physicochemical standpoints.…”
Section: Introductionmentioning
confidence: 99%